Improvement of Creative Thinking Ability of Students with LKPD Based on Curious Note Program Learning Model - Farumananda, Fatimah Primadian; Wiyanto, Wiyanto; Darma Putra, Ngurah Made; Hidayah, Noor (Postgraduate, Universitas Negeri Semarang, Indonesia, 2019)
The ability to think creatively is one of the 21st century abilities that students must have. Curious Note Program (CNP) learning model helps students to maintain the creativity and scientific ability of students.  This research aims to determine the improvement of students' creative thinking skills through student worksheets (LKPD) based on Curious Note Program learning model. This research design uses One Group Pre-Posttest. The instrument data collection uses LKPD based on CNP learning model and a description of the ability to think creatively. The research subjects used were students of class X in Temanggung State MA in the academic year 2017/2018.  The results showed that through LKPD based on the CNP learning model it could improve students' creative thinking skills with n-gain of 43% in the medium category. Meanwhile, to increase each indicator based on the acquisition of n-gain of 27% fluency in the low category, 37% flexibility in the medium category, originality 22% in the low category and elaboration 56% in the medium category.